2002
DOI: 10.1007/s00246-001-0010-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atrial Septal Defect Closure Using Amplatzer Septal Occluder with Surgery

Abstract: Our study reports the results of a comparison of closure of atrial septal defect (ASD) surgically with transcatheter closure using the Amplatzer septal occluder. Patients having an ASD and a surgical closure or transcatheter closure between January 1999 and July 2000 were selected. There were 103 patients who had ASD. All 64 patients in group 1 (surgery) had a successful operation, with only 2 patients with a mild residual shunt. There were 39 patients enrolled for transcatheter closure of the ASD (group 2). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 0 publications
0
18
0
5
Order By: Relevance
“…Catheter guided ASD repair is preferred over the open surgical alternative because of decreased morbidity and mortality without the sacrifice of efficacy [1][2][3][4]. The success of the procedure is reliant upon proper patient selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter guided ASD repair is preferred over the open surgical alternative because of decreased morbidity and mortality without the sacrifice of efficacy [1][2][3][4]. The success of the procedure is reliant upon proper patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter atrial septal defect (ASD) closure has been demonstrated to be safe, efficacious and associated with lower morbidity and cost when compared to surgical closure [1][2][3][4]. However, procedural success is predicated on proper patient selection for which accurate non-invasive imaging assessment is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…After multicentre clinical trials, the device was approved by the United States Food and Drug Administration (FDA) in 2002 for use in children and adults. For transcatheter closure using the Amplatzer septal occluder, additional criteria are that the ASD II diameter is not excessively large for currently available devices, and there should be a distance of>5 mm from the margins of the defect to the coronary sinus, atrioventricular valves and right upper pulmonary vein [4, 5]. The contraindications for percutaneous closure include too big defect or too small surrounding rims (except for the anterior rim toward the aorta).…”
Section: Introductionmentioning
confidence: 99%
“…Mean CPB time and mean aortic cross-clamp time were standard for this procedure (14,24). Residual early and late atrial shunts after surgical closure were rare (32,33).…”
Section: Discussionmentioning
confidence: 99%